LMNB2-mediated high PD-L1 transcription triggers the immune escape of hepatocellular carcinoma - Yuxuan Li; Jie Zhu; Fengguang Zhai; Yidong Ge; Ziqing Zhan; Shuyan Wang; Lili Kong; Jianan Zhao; Lecheng Hu; Siyuan Wang; Jiaxin Shi; Jianing Mao; et al. (Cell Death Discovery)
Abstract While immune checkpoint inhibitors targeting programmed cell death-ligand 1 (PD-L1) demonstrate clinical efficacy in hepatocellular carcinoma (HCC), tumor cells frequently evade immune surveillance through PD-L1 overexpression, a phenomenon whose regulatory mechanisms remain poorly understood. Through integrated analysis of single-cell transcription sequence data, we identified aberrant upregulation of Lamin B2 (LMNB2) specifically in immunotherapy-sensitive HCC patients. Functional characterization revealed that LMNB2 acts as a transcriptional regulator of PD-L1, potentiating immune escape mechanisms in HCC cells during co-culture with Jurkat cells. Notably, we discovered that speckle-type POZ protein (SPOP) directly interacts with LMNB2 to mediate its ubiquitination and proteasomal degradation, thereby maintaining physiological PD-L1 expression levels. Clinically relevant SPOP mutations or reduced SPOP expression impaired this regulatory mechanism, leading to LMNB2 accumulation and subsequent PD-L1 hyperactivation. Importantly, combinatorial targeting of LMNB2 with Atezolizumab (PD-L1 inhibitor) displayed a synergistic effect on suppressing tumor progression both in vitro and in vivo, particularly in HCC models with SPOP mutations or LMNB2 overexpression. These findings unveil a novel ubiquitination-dependent regulatory axis in HCC immune evasion and propose targeted co-inhibition strategies to overcome HCC immunotherapy resistance.